Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
=\(\dfrac{1}{2009.\left(\dfrac{1}{2009}+\dfrac{1}{2011}+\dfrac{1}{2010}\right)}+\dfrac{1}{2010.\left(\dfrac{1}{2010}+\dfrac{1}{2009}+\dfrac{1}{2011}\right)}+\dfrac{1}{2011.\left(\dfrac{1}{2011}+\dfrac{1}{2009}+\dfrac{1}{2010}\right)}\)\(=\dfrac{1}{2009}:\left(\dfrac{1}{2009}+\dfrac{1}{2010}+\dfrac{1}{2011}\right)+\dfrac{1}{2010}:\left(\dfrac{1}{2009}+\dfrac{1}{2010}+\dfrac{1}{2011}\right)+\dfrac{1}{2011}:\left(\dfrac{1}{2009}+\dfrac{1}{2010}+\dfrac{1}{2011}\right)\)
\(=\left(\dfrac{1}{2009}+\dfrac{1}{2010}+\dfrac{1}{2011}\right):\left(\dfrac{1}{2009}+\dfrac{1}{2010}+\dfrac{1}{2011}\right)=1\)
Kết quả : 0
Giải:
(-2012+2012)+(-2011+2011)+(-2010+2010)+(-2009+2009)+................+(-3+3)+(-2+2)+(-1+1)+0=0
Có : \(2009+2010>\dfrac{2009}{2010}\) ; \(2011+2012>\dfrac{2011}{2012}\)
\(\dfrac{2011}{2010}>1\) ; \(\dfrac{2010}{2011}< 1\) \(\Rightarrow\dfrac{2011}{2010}>\dfrac{2010}{2011}\)
Ta có : \(2009+2010+\dfrac{2011}{2010}+2011+2012>\dfrac{2009}{2010}+\dfrac{2010}{2011}+\dfrac{2011}{2012}\)
\(\Leftrightarrow B>A\)
Hay \(A< B\)
S=(2010+2010^2)+(2010^3+2010^4)+...+(20010^2009)+(2010^2010)
=2010(1+2010)+2010^3(1+2010)+...+2010^2009(1+2010)
=2010.2011+2010^3.2011+...+2010^2009.2011
=2011(2010+...+2010^2009) chia hết 2011
nha
A = 20102011 - 20102010
A = 20102010 .( 2010 - 1)
A = 20102010.2009
2009 ⋮ 2009 ⇒ A = 20102010.2009 ⋮ 2009
2011 × 2010 - 1 / 2009 × 2011 + 2010
=2011 × 2009 + 2011 - 1 / 2009 × 2011 + 2010
= 2011 × 2009 + (2011 - 1) / 2009 × 2011 + 2010
= 2011 × 2009 + 2010 / 2009 × 2011 + 2010
= 1